2018
DOI: 10.1093/jee/toy135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Entomopathogenic Fungi Metarhizium anisopliae, Beauveria bassiana and Isaria sp. for the Management of Aphis craccivora (Hemiptera: Aphididdae)

Abstract: Cowpea, Vigna unguiculata ((L.) Walp; Fabales: Fabaceae), is an important indigenous vegetable and grain legume in the tropics where it represents a major diet component. Cowpea aphid, Aphis craccivora (Koch; Hemiptera: Aphididdae) is a major pest causing up to 100% yield losses. Aiming at establishing alternative approach to synthetic insecticides, we evaluated the pathogenicity of 23 fungal isolates including Metarhizium anisopliae ((Metschn.) Sorokin; Hypocreales: Clavicipitaceae), Beauveria bassiana ((Bals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…isolate ICIPE 62 in the management of A. craccivora under field conditions. The efficacy of this isolate in inducing high mortality on A. craccivora and other aphid species has been also demonstrated under laboratory conditions and screenhouse in previous studies (Bayissa et al, ; Mweke et al, ). Application of both M. anisopliae ICIPE 62 formulations did not result in significant decline in aphid densities in wet season compared to untreated control.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…isolate ICIPE 62 in the management of A. craccivora under field conditions. The efficacy of this isolate in inducing high mortality on A. craccivora and other aphid species has been also demonstrated under laboratory conditions and screenhouse in previous studies (Bayissa et al, ; Mweke et al, ). Application of both M. anisopliae ICIPE 62 formulations did not result in significant decline in aphid densities in wet season compared to untreated control.…”
Section: Discussionsupporting
confidence: 58%
“…Fungal isolate ICIPE 62 ( Metarhizium anisopliae s.l. ) used in this study was obtained from icipe's Arthropod Germplasm Centre and was recently demonstrated to be pathogenic against A. craccivora under laboratory conditions (Mweke et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations